Supremely American : popular song in the 20th century : styles and singers and what they said about America - Tawa, Nicholas E. (Lanham, Md. : Scarecrow Press, 2005)
This is a study of the way in which popular words and music relate to American life. The question of what popular song was, and why it came into existence, as well as how each song fit within the context of the larger 20th Century society are considered and explained clearly and fruitfully. Songs of the Jazz Age and Swing Era are considered primarily in terms of song-types and their relation to the times. Post World War II songs are shown to have splintered into a multitude of different styles and variations within each style. Many 20th Century songs came to be closely identified with particular singers and performance groups, shifting the attention to the styles identified with particular performers and the audiences they reached. Tawa avoids overly-technical vocabulary, making this examination of hundreds of popular songs accessible to a wide variety of readers seeking to better their understanding of the often perplexing musical landscape of the time [Publisher description].
Preliminary considerations -- A closer look at the jazz age -- Swing time -- Change : different music cultures come to the fore -- White-American and British songs in a decade of turmoil -- Black-American music comes to the fore in the 1960s -- Out of the seventies -- The eighties and nineties -- A temporary ending.
Includes bibliographical references (pages 315-321) and index.
Keywords: Popular music -- United States -- History and criticism